Development of solid state automatic controller for single phase generator / Mohammad Fakharurazi Shafiie - Shafiie, Mohammad Fakharurazi (1995)
The objective of this project is to improved an automatic control system for Single Phase Generator. The designing and developing of the fully automatic system is expected to enhance the usage of the standby generator and its application in domestic and industrial will be widened. The jobs involved the development and design of the solid state controller, construct of PCB circuit using smartwork software, hardware development and interfacing of relay. The system developed, will be able to activate a Single Phase Generator to provide an automatic backup supply during power failure. The solid state controller is operated by using sensor, voltage comparator, timer and decade counters to control a bank of relays.